A new look at effective interactions between microgel particles. Issue 1 (December 2018) - Bergman, Maxime; Gnan, Nicoletta; Obiols-Rabasa, Marc; Meijer, Janne-Mieke; Rovigatti, Lorenzo; Zaccarelli, Emanuela; Schurtenberger, Peter
Abstract Thermoresponsive microgels find widespread use as colloidal model systems, because their temperature-dependent size allows facile tuning of their volume fraction in situ. However, an interaction potential unifying their behavior across the entire phase diagram is sorely lacking. Here we investigate microgel suspensions in the fluid regime at different volume fractions and temperatures, and in the presence of another population of small microgels, combining confocal microscopy experiments and numerical simulations. We find that effective interactions between microgels are clearly temperature dependent. In addition, microgel mixtures possess an enhanced stability compared to hard colloid mixtures - a property not predicted by a simple Hertzian model. Based on numerical calculations we propose a multi-Hertzian model, which reproduces the experimental behavior for all studied conditions. Our findings highlight that effective interactions between microgels are much more complex than usually assumed, displaying a crucial dependence on temperature and on the internal core-corona architecture of the particles. Changing temperature of thermoresponsive microgels is typically used as a proxy for modifying volume fraction based on the assumption that doing so does not alter the interaction potential. Bergman et al. shows that this picture is oversimplified and microgels are better described by a multi-Hertzian model.